The Effect of Kaneta Media Implementation on the Early Reading Ability of Children - Vita Fatimatuz Zahroh; Choirun Nisak Aulina (Jurusan PIAUD IAIN Syekh Nurjati Cirebon, 2021)
Early reading skills are one of the most important language developments to be developed in early childhood. This can be done through appropriate stimulation of learning, one of which is the accuracy in using learning media. The purpose of this study is to analyze whether there is an effect of the application of Kaneta media (Smart Flannel Bags) on children's early reading ability. This study used a pre-experimental quantitative method type one-group pretest-posttest design. The population of this research is the children of group A TK Dharma Wanita Persatuan Kedungboto, Porong District with saturated sampling technique with a total of 20 students. The data collection technique in this study used the results of the preliminary reading ability test. The data analysis technique used the dependent t test with the research results t count = 10.87 and t table = 2.093 so that tcount > t table, which means H1 is accepted and H0 is rejected. The results showed that the application of Kaneta media had an effect on children's pre-reading abilities, so teaching early reading in early childhood could be done using Kaneta media.